Analysis of Students’ Perception of Online Learning (A Study of three universities in Aceh) - Teuku Azhari; Kurniawati, S.Pd., M.A (Sean Institute, 2021)
This study analyzed students’ perception of online learning in three universities in Aceh, IAIN Takengon, Malikussaleh University, and Samudera University. It studied how they perceived the application of online learning during the Covid-19 pandemic. In analyzing their perception, researchers considered three aspects of perception; learning process, learning environment, and learning motivation. To gather the data and information, researchers designed a self-administered questionnaire consisting of 16 items to the respondents online using Google Form. In addition, a discussion in the form of FGD with respondents was conducted in each site to gain a more comprehensive insight on the subject. A total of 449 respondents from three universities participated in the questionnaires. Researchers utilized purposive random sampling under the criteria of active students who have experienced online learning on campus. Some students who have responded to the questionnaires were then invited for FGD in each of the universities. Researchers utilized SPSS software to analyze the data and present the phenomenon and general findings to be elaborated in the study. The results of the study uncovered that students have a negative attitude towards online learning in the learning process, learning environment, and learning motivation. However, the learning process has a positive correlation with both the learning environment and learning motivation.